A Combination of Micro-Credit and Micro-Training with mediating role of Formal Education: A Micro-Enterprise Success Formula - Hameed, Waseem Ul; Hussain, Tanveer; Azeem, Muhammad; Basheer, Muhammad Farhan; Arif, Muhammad (2017)
This study aims at giving an overview of the emerging research field of microfinance in a phase that is still very fluid in micro-enterprises. The ultimate objective of this study is to develop a distinctive formula (framework) for micro-enterprise success.As the success of micro-enterprise is under debate from many decades, but the researchers and entrepreneurs are unable to find the unique factor to develop a comprehensive framework. Previous research studies on relationship of different success factors and small business success are missing by comprehensive framework.It is important to identify the measure of success which is still undefined. Four hypotheses are proposed concerning the relationship of micro-enterprise success and microfinance factors (i.e., micro-credit, micro-training) with mediating role of formal education. These hypotheses predicting a positive relationship between micro-enterprise success and microfinance factors. However, among all other microfinance factors (i.e., micro-saving, micro-insurance, social capital), micro-credit and micro-training has relatively higher effect on microenterprise performance followed by level of education. Hence, this study contributing in the body of knowledge by developing a micro-enterprise success formula for researchers and entrepreneurs, which ultimately improve the performance of microenterprises.